The Possibilities of COBIT and ITIL Frameworks Combination in IT Service Management - Shinkariuk, Egor; Svatá, Vlasta, 1952-; Vondrová, Iva; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2023)
IT service management frameworks, notably COBIT and ITIL, have long served as industry standards, adapting to evolving trends in Information Technologies. The latest iterations, ITIL 4 and COBIT 2019, signify the ongoing development in response to modern IT challenges. This thesis aims to thoroughly study and compare COBIT and ITIL. The primary objective is to assess the feasibility and practicality of integrating select elements from both frameworks into a cohesive IT Service Management practice. By exploring potential synergies, the research aims to contribute valuable insights to organizations seeking an optimal approach to managing IT services. To support these ideas, a detailed survey with a diverse group of IT professionals was conducted, using both qualitative and quantitative methods. The survey responses were systematically analyzed, providing an understanding of practitioners' perspectives on the compatibility, advantages, and challenges associated with combining elements from COBIT and ITIL.
Vedoucí práce: Vlasta Svatá
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: informační systémy a technologie [obor dipl. práce]; diplomové práce; master's theses